2013
DOI: 10.14774/jkiid.2013.22.6.212
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Fashion Shops' Images Applying Gaze Frequency

Abstract: This study uses a fashion shop facade design to track human gaze, find gaze frequency for gaze time for the gaze points along the path of sight, and expose the importance of facade design and figure out the value through theoretical systematization. Thus, this study employed the measurement method in physiological psychology which is sight-tracking device with eye-tracking to perform effective data evaluation. To find gaze frequency and study the contents to reflect on the facade, precedent study review, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A sequence of five trials was displayed on a 15-inch monitor. Each trial showed a presentation of an exterior image (722 3 722 pixels) for 10 s (Yeo and Oh, 2013). Before moving to the next trial, a fixation cross was presented in the middle of the monitor screen for 5 s. No instruction was given during the eye-tracking experiment to let participants notice the stimuli without goal orientation (Orquin and Loose, 2013).…”
Section: Eye-tracking and Stimulimentioning
confidence: 99%
See 1 more Smart Citation
“…A sequence of five trials was displayed on a 15-inch monitor. Each trial showed a presentation of an exterior image (722 3 722 pixels) for 10 s (Yeo and Oh, 2013). Before moving to the next trial, a fixation cross was presented in the middle of the monitor screen for 5 s. No instruction was given during the eye-tracking experiment to let participants notice the stimuli without goal orientation (Orquin and Loose, 2013).…”
Section: Eye-tracking and Stimulimentioning
confidence: 99%
“…This suggests that participants tended to spend most of the time looking at the upper board followed by the center and the lower board with no significant difference, and then the side board. On the other hand, for the frontage images of apparel store, viewers pay more attention to the middle position than others (Yeo and Oh, 2013).…”
Section: Eye-movement Analysis On the Area Of Interests In The Façadementioning
confidence: 99%